Streamlined request services: the integration of ILS, ILL and Consortia borrowing systems. Issue 3 (10th August 2015) - Ye, Gan (Grace); Bryant, Sally
Abstract : Purpose: – This paper aims to study streamlined request services based on discrete systems' integration in an academic library. The integration of discrete systems allows patrons to use the library's online public access catalog to send requests and have the requests automatically transferred to the local integrated library system (ILS), the consortia borrowing system, and an interlibrary loan system. The integration of discrete systems also allows adding the consortia service without adding any library staff. Design/methodology/approach: – The authors introduce library holdings behind the search interface, the discrete library systems and the authentication system. The paper illustrates how patron requests can be automatically transferred to discrete library systems. Findings: – Resource sharing has become a hot topic in the library world where libraries are facing budget cuts, space limits and employee shortage challenges. Systems' integration will help libraries to add new services without adding staff. Practical implications: – The consortia borrowing system can be seamlessly integrated into discrete library systems and a campus authentication system. Pepperdine University's experience can serve as an example for libraries which have a plan to implement consortia borrowing systems or want to streamline their workflows. Originality/value: – This paper takes a fresh look at the traditional request services using cloud-based systems.